Cognitive deficits profiles in the first-episode of schizophrenia, clinical high risk of psychosis, and genetically high-risk of psychosis - Dong, Fang; Mao, Zhen; Ding, Yushen; Wang, Lu; Bo, Qijing; Li, Feng; Wang, Feifei; Wang, Chuanyue (Frontiers in Psychiatry, 2023)
Background: Cognitive deficits are core characteristics of schizophrenia, presenting before the emergence of psychotic symptoms. Individuals with a clinical high-risk for psychosis (CHR) and genetically high-risk of psychosis (GHR) also exhibit cognitive impairments. Nonetheless, it remains uncertain in which domains of cognitive impairments in these two groups were more similar to those of schizophrenia patients. Moreover, it is unclear which domains of impairment are caused by quality factors and which are more related to the state of disease. This research initiative aimed to extensively examine the distinct cognitive impairment profiles among the CHR, GHR, and first-episode schizophrenia (FES) cohorts. Method: We compared the cognitive functions of the three groups and a healthy control group (HCs) using the MATRICS Consensus Cognitive Battery (MCCB). Our sample consisted of 56 patients with FES, 42 with CHR, 26 with GHR, and 62 HCs. Results: Individuals with FES, GHR, and CHR showed significant impairment across the majority of MCCB domains, with the exception of visual learning, in comparison to HCs. None of the MCCB domains demonstrated a discerning ability to accurately differentiate between individuals with CHR and those with GHR. In the speed of processing and attention/vigilance domains, individuals with GHR and CHR exhibited scores between those of FES and HCs, indicating an intermediate level of cognitive function. Conversely, the levels of impairment observed in working memory and verbal learning were relatively consistent across all the three groups. Notably, individuals in the CHR group exhibited performance akin to that of the HCs in the reasoning/problem-solving domain, while also manifesting significant differences from the FES group. Additionally, individuals with GHR displayed performance in social cognition similar to that of the HCs, while also demonstrating significant distinctions from the FES group. Conclusion: Significant cognitive deficits exist in individuals with CHR, GHR, and FES, and these deficits vary across domains. Processing speed and attention/vigilance could potentially serve as robust biomarkers for identifying individuals at a risk of psychosis. The impairment observed in reasoning/problem-solving abilities might signify a qualitative trait, whereas deficits in social recognition could indicate a state characteristic specific to schizophrenia.